Hormesis can and Does Work in Humans - Suresh I. S. Rattan; Dino Demirovic (SAGE Publishing, 2010)
If we accept the validity of the general concept of physiological hormesis as being the phenomenon of achieving health beneficial effects by exposure to mild stress, then hormesis is being applied already and successfully to humans. The evidence for this is the well-demonstrated health benefits of regular and moderate exercise. Mild stress-induced activation of one or more intracellular pathways of stress response are central to this. Experimental studies performed on human cells in culture exposed to mild heat shock and other stresses provide biochemical and molecular evidence in support of the application of hormesis to human systems. Although several issues remain to be resolved by more research with respect to the extent and duration of hormetic exposure, making use of the cellular stress response pathways can facilitate discovering novel hormetins for human applications.